Two new species of Siconema (Drilonematoidea: Ungellidae) parasitic in earthworms in Vietnam, and systematic relationships as inferred from ribosomal sequence data - Ivanova, E. S.; van Luc, Pham; Spiridonov, S. E. (Zootaxa, 2012)
Two new species of Siconema (Drilonematoidea: Ungellidae) from Pu Mat Nature Reserve, Vietnam are described andillustrated. Siconema ovicallosum sp. n. is characterised by a wide female body, female caudal organs displaced toposterior extremity followed by short tail tip; males short, slim with caudal organs near cloacal opening and long, conicalposterior portion of tail; cephalic hooks in both sexes with sturdy base and thin, diverging blade tips; tubular stomaincorporated in hooks base; eggs with very thick shells and two suberose polar caps. It is most similar to S. laticaudatumIvanova & Pham Van Luc, 1997 but is distinguished by much smaller males, their caudal organs, and the shape andornamentation of eggshells. Siconema diducuncinum sp. n. is characterised by a stoma that is confined in a tube thatprotrudes between thin hooks with widely distributed blades, caudal organs situated at long distance from the tail tip, eggsin the shape of a double-poled elongated lemon and presence of a copulatory disc in males. Siconema diducuncinum sp.n. is most closely related to S. sinense Timm, 1966 but differs from it by having rounded vs elongate pharyngeal bulb,thinner and smoother eggshells with more pronounced polar caps, twisted vs straight ovary and a copulatory disc in males.By an elongated tail spike and bristling hook blades, S. diducuncinum sp. n. shares similarities with S. neozelandicumYeates & Spiridonov, 1996 but differs in having a non-amalgamated hook base, presence of projecting stomatal tube,differently ornamented eggshells and a copulatory disk in males. A key to species of Siconema is given. Phylogenetic relationships of the new species and other drilonematids are discussed.